2018
DOI: 10.1073/pnas.1809540115
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the super relaxed state of human β-cardiac myosin and the mode of action of mavacamten from myosin molecules to muscle fibers

Abstract: Mutations in β-cardiac myosin, the predominant motor protein for human heart contraction, can alter power output and cause cardiomyopathy. However, measurements of the intrinsic force, velocity, and ATPase activity of myosin have not provided a consistent mechanism to link mutations to muscle pathology. An alternative model posits that mutations in myosin affect the stability of a sequestered, super relaxed state (SRX) of the protein with very slow ATP hydrolysis and thereby change the number of myosin heads a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
458
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 304 publications
(501 citation statements)
references
References 74 publications
40
458
1
2
Order By: Relevance
“…Quantitative epi‐fluorescence studies, measuring single nucleotide turnovers, have revealed a new form of highly inhibited state of myosin termed as the SRX, with extremely low ATP turnover rates (> 100 s) . In SRX, the myosin heads are highly ordered and interact with one another along the axis of the thick filament forming structures known as the interacting heads motifs (IHMs) . This recently discovered SRX state of myosin motor was shown to be disrupted by myosin RLC phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative epi‐fluorescence studies, measuring single nucleotide turnovers, have revealed a new form of highly inhibited state of myosin termed as the SRX, with extremely low ATP turnover rates (> 100 s) . In SRX, the myosin heads are highly ordered and interact with one another along the axis of the thick filament forming structures known as the interacting heads motifs (IHMs) . This recently discovered SRX state of myosin motor was shown to be disrupted by myosin RLC phosphorylation .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many HCM mutations, R58Q does not fall into a typical ‘hypercontractile' category, as it does not weaken the SRX‐IHM state to produce more functionally accessible heads . A common mechanism via which different sarcomeric proteins may induce the development of HCM has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mavacamten (MyoKardia, Inc., South San Francisco, CA, USA), a first‐in‐class oral small molecule, targets this process directly as an allosteric modulator of cardiac β‐myosin, causing reversible inhibition of actin–myosin cross bridging . In animal models, treatment with mavacamten reduced contractility, eliminated SAM, relieved LVOT obstruction, and improved the myocardial pressure–volume relationship ( Figure C ) .…”
Section: Novel Pharmacotherapies For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…In relaxed muscle where the heads are unable to bind to the tropomyosin.troponin (Tm.Tn) regulated thin filaments, the open state heads are disordered (disordered relaxed state, DRX) and believed to be turning over ATP at a rate of ~ 0.03 s -1 (two orders of magnitude slower than the actin-activated rate of ~ 3 s -1 ), while the heads in the IHM state are believed to be in a super relaxed state (SRX) with an even lower ATP turnover of ~ 0.003 s -1 (14,15). Thus, SRX is defined as a very slow ATP turnover state of myosin as measured by a fluorescent-ATP assay (14), while IHM is a structural state in which the myosin heads fold on their own tail leading to an off state of the thick filament.…”
Section: Introductionmentioning
confidence: 99%